INOVASI JAMINAN KESEHATAN SEMESTA DALAM USAHA MENINGKATKAN KUALITAS PELAYANAN KESEHATAN BAGI PESERTA JAMINAN PENYANGGA DI DAERAH ISTIMEWA YOGYAKARTA - Nova Lestari; Yanuardi Yanuardi (Yogyakarta State University, 2017)
This research aims to know and understand about the implementation of the innovation of Universal Health Insurance (Jamkesta) system in an effort to improve health care quality for participants buffer in Yogyakarta. This reseach used descriptive qualitative method. Data collected by interview and observation. Data validity checking is done through a method of triangulation. The process of data analysis include data reduction, data presentation, and conclusion. The results showed that the element of human resources, processes, financing, location, response to suggestions for improvements innovation, law, and social supports the implementation of Universal Health Insurance for participant buffer and newborns. However, there are still some deficiencies that need to be corrected when viewed from the elements of socialization, culture and technology. Meanwhile, elements of the results showed that as many as 45% of the total number of participants for eligibility letter (SEP) printed out by Bapel Jamkesos is for the class buffer without ID cards and newborns. This indicates that the Jamkesta vision and mandate of the Governor of Yogyakarta has been reached.Keywords: Innovation, Universal Health Insurance, and Health Care.